2017
DOI: 10.1021/acsnano.7b03131
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization, Reentrant Melting, and Resolubilization of Virus Nanoparticles

Abstract: Crystallization is a fundamental and ubiquitous process that is well understood in the case of atoms or small molecules, but its outcome is still hard to predict in the case of nanoparticles or macromolecular complexes. Controlling the organization of virus nanoparticles into a variety of 3D supramolecular architectures is often done by multivalent ions and is of great interest for biomedical applications such as drug or gene delivery and biosensing, as well as for bionanomaterials and catalysis. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 79 publications
3
55
0
Order By: Relevance
“…Since this re-entrant transition is reproduced by our mean-field theory, which assumes local equilibrium at the molecular scale, we emphasize that the re-entrant melting transition should be generic to systems in which assembly is due to weak, multivalent binding mediated by free molecules in solution. Indeed qualitatively similar behavior is observed in a wide range of experimental systems, ranging from 'squelching' in gene expression [31] to re-entrant condensation in proteins [32] and nucleic acids [33] to selfassembly of virus particles [34]. Thus our model may find applications in a number of other settings.…”
Section: Discussionsupporting
confidence: 68%
“…Since this re-entrant transition is reproduced by our mean-field theory, which assumes local equilibrium at the molecular scale, we emphasize that the re-entrant melting transition should be generic to systems in which assembly is due to weak, multivalent binding mediated by free molecules in solution. Indeed qualitatively similar behavior is observed in a wide range of experimental systems, ranging from 'squelching' in gene expression [31] to re-entrant condensation in proteins [32] and nucleic acids [33] to selfassembly of virus particles [34]. Thus our model may find applications in a number of other settings.…”
Section: Discussionsupporting
confidence: 68%
“…The process of formation of virus particles in which the protein subunits encapsidate genome (RNA or DNA) to form a stable, protective shell called the capsid is an essential step in the viral life cycle [1][2][3]. The capsid proteins of many small single-stranded (ss)RNA viruses spontaneously package their wild-type (wt) and other negatively charged polyelectrolytes, a process basically driven by the electrostatic interaction between positively charged protein subunits and negatively charged cargo [4][5][6][7][8][9]. Understanding the phenomena of formation of viral particles is of great interest due to their potential applications in nanomedicine and biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…How exactly capsid proteins (CPs) assemble to assume a specific size and symmetry have been investigated for over half a century now [20,21]. Since the self-assembly of virus particles involves a wide range of thermodynamics parameters, different time scales and an extraordinary number of possible pathways, the kinetics of assembly has remained elusive, linked to Levinthal's paradox for protein folding [8,[22][23][24]. The role of the genome on the assembly pathways and the structure of the capsid is even more intriguing [5,[25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…This barrier is significantly lower for a synthetic polyelectrolyte, such as poly(styrene sulfonic acid), as compared to RNA genome, but the resulting structure lacked the icosahedral symmetry. In other TR-SAXS studies, the crystallization of wild type SV40 virus particles to body-centered cubic (bcc) structure upon dialysis with MgCl 2 and their reentrant melting at higher MgCl 2 concentrations were investigated [85]. Thermodynamic modeling of the transition at different salt concentrations suggested that the entropy of counterions is the driving mechanism.…”
Section: Assembly Of Biomacromolecular Complexesmentioning
confidence: 99%